Jesus and the land: the New Testament challenge to "Holy Land" theology - Burge, Gary M. (SPCK, 2011)
Jesus and the Land will help Christians to form a biblical view about modern-day claims to the land in Israel-Palestine. Examining what the New Testament says about the idea of land being 'holy', this guide is accessible and non-technical